2021
DOI: 10.3390/jcm10040863
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA): Surgical Outcomes and Learning Curve

Abstract: The transoral endoscopic thyroidectomy vestibular approach (TOETVA) has excellent cosmetic effects and its popularity is increasing worldwide. We present our experience with TOETVA and its short-term outcomes. This study included 110 consecutive patients who underwent TOETVA at a single institution between July 2016 and June 2020. We analyzed clinicopathologic data, short-term postoperative outcomes, and learning curve using cumulative summation (CUSUM) analysis. Of the 110 patients who underwent TOETVA, 101 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
(28 reference statements)
0
37
0
1
Order By: Relevance
“…TOETVA procedures after working space formation have been described in detail in previous studies (1,3,13). In brief, after creating the working space, the midline of the strap muscles was divided.…”
Section: Surgical Procedures After Working Space Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…TOETVA procedures after working space formation have been described in detail in previous studies (1,3,13). In brief, after creating the working space, the midline of the strap muscles was divided.…”
Section: Surgical Procedures After Working Space Formationmentioning
confidence: 99%
“…However, the process of flap dissection for creating working space can be particularly technically challenging. Because forming working space in TOETVA involves a very small space and increased risk of bleeding, it requires the surgeon to overcome a steep learning curve and may be especially difficult for surgeons with little experience with remote-access surgeries (3).…”
Section: Introductionmentioning
confidence: 99%
“… 11 Though invasive procedure for assessing of vocal cord function as laryngoscopy might not be used in all institutes or worldwide as Chai and colleagues recently reported routine rigid laryngoscope for assessing of vocal cord mobility. 33 Generally, assessment of the vocal cord function by laryngoscopy could be used. In our study, the vocal cord function was confirmed by combined modalities such as TLUSG visualization, IONM, and laryngoscopy in symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the operation period was prolonged in the same report, it was shown in several studies that the operation time decreased with adequate preparation and practice due to the TOETVA’s low learning curve. [ 27 , 28 ] Numerous multicenter researches verifying the safety and effectiveness of TOETVA are continued to be conducted and larger-scale randomized controlled trials remain necessary due to the small number of case. [ 29 - 31 ]…”
Section: Discussionmentioning
confidence: 99%